Prospective study of the innate cellular immune response in low vaccine responder children. Issue 1 (January 2017) - Surendran, Naveen; Nicolosi, Ted; Kaur, Ravinder; Morris, Matthew; Pichichero, Michael
We recently reported our findings from a longitudinal, prospective study where we identified 10% infants who were low vaccine responders (LVR) at age 9–12 mo following routine primary series vaccine schedule. We found multiple cellular deficiencies in LVR children, including low number of memory B cells, reduced polyclonal stimulation of naïve/memory T cell response and suboptimal APC response. These children outgrew their poor vaccine response by the time they received booster doses of vaccine. Studies in human infant innate immunity are rare because of the unique challenges in specimen collection. As innate immunity instructs adaptive immunity, we hypothesized that the primary immune defect lies with innate immunity and in this study we sought to determine the ontogeny of innate immune response in LVR children between 6 and 36 mo of age. Interestingly, suboptimal APC response observed in LVR children at 6–9 mo of age characterized by significantly ( P < 0.05) low basal MHC II expression, low R848 induced IRF7 fold change, as well as low IFN-α, IL-12p70 and IL-1β levels, came to parity with normal vaccine responders by 12–15 mo of age, suggesting that the observed immune deficiency in LVR children may be the result of delayed maturation of immune system.